Front Cover: Transportable Strontium Optical Lattice Clocks Operated Outside Laboratory at the Level of 10−18 Uncertainty (Adv. Quantum Technol. 8/2021). Issue 8 (10th August 2021) - Ohmae, Noriaki; Takamoto, Masao; Takahashi, Yosuke; Kokubun, Motohide; Araki, Kuniya; Hinton, Andrew; Ushijima, Ichiro; Muramatsu, Takashi; Furumiya, Tetsuo; Sakai, Yuya; Moriya, Naoji; Kamiya, Naohiro; et al.
Abstract : Laser cooled and trapped atoms in an optical lattice operated at the magic wavelength, as illustrated in the cover image, play a leading part in an ultraprecise optical clock, referred to as an optical lattice clock. In article number 2100015, Noriaki Ohmae and co‐workers developed transportable optical lattice clocks that were operated outside a laboratory with a fractional uncertainty of 5.5 × 10 −18 . Their demonstration will accelerate field applications of ultraprecise optical clocks, such as a chronometric leveling.